2010
DOI: 10.1002/mrm.22550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise intervention on thigh muscle volume and anatomical cross‐sectional areas—Quantitative assessment using MRI

Abstract: The objective of this study was to evaluate the location-specific magnitudes of an exercise intervention on thigh muscle volume and anatomical cross-sectional area, using MRI. Forty one untrained women participated in strength, endurance, or autogenic training for 12 weeks. Axial MR images of the thigh were acquired before and after the intervention, using a T1-weighted turbo-spin-echo sequence (10 mm sections, 0.78 mm in-plane resolution). The extensor, flexor, adductor, and sartorius muscles were segmented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 27 publications
3
64
2
Order By: Relevance
“…Therefore, from investigations implementing 12 weeks of either resistance or aerobic exercise training, both modes of exercise have elicited a similar increase in quadriceps muscle volume suggesting that both modes of exercise are equally effective at stimulating hypertrophy in the muscles utilized over 12 weeks. These findings are supported by Hudelmaier et al (20) and remain consistent with exercise programs of 6 months duration (29, 33). Collectively, studies observing skeletal muscle growth after aerobic exercise training observe an average increase of over 7% (Table 1), which is comparable to the hypertrophy after resistance exercise training (25, 29, 37).…”
Section: Skeletal Muscle Hypertrophysupporting
confidence: 85%
“…Therefore, from investigations implementing 12 weeks of either resistance or aerobic exercise training, both modes of exercise have elicited a similar increase in quadriceps muscle volume suggesting that both modes of exercise are equally effective at stimulating hypertrophy in the muscles utilized over 12 weeks. These findings are supported by Hudelmaier et al (20) and remain consistent with exercise programs of 6 months duration (29, 33). Collectively, studies observing skeletal muscle growth after aerobic exercise training observe an average increase of over 7% (Table 1), which is comparable to the hypertrophy after resistance exercise training (25, 29, 37).…”
Section: Skeletal Muscle Hypertrophysupporting
confidence: 85%
“…However, a number of studies have demonstrated that single-slice ACSA is predictive of muscle volume and that muscle ACSA measurements are predictive of muscle strength and joint moments, and are sensitive to changes due to disuse/training. 7,8,11,16,27 In our study, the ACSA for the vastus medialis might have been underestimated, which could have influenced our findings related to the QuadML ACSA ratio but is unlikely to have influenced those related to the QH ACSA ratio, because mid-thigh ACSA is considered adequate for overall quadriceps and hamstrings volume. 11 We also did not take into consideration fascicle length and pennation angle, which are used to calculate physiological CSA.…”
Section: Discussionmentioning
confidence: 65%
“…Binding of these ligands normally initiates a signaling cascade that results in decreased muscle growth 7. A single dose of bimagrumab increases muscle mass in healthy young men similar to that achieved with 12 week of high-intensity resistance training (8, 9), and in sedentary middle-aged adults, equivalent to that achieved with 9 months of jogging 12–20 miles per week (10). It has also been shown to work in elderly people; and, in a single leg casted model in healthy young men, bimagrumab improved recovery from atrophy.…”
Section: Targeting the Underlying Biology Of Sarcopeniamentioning
confidence: 90%